Pharmaceutical removal in tropical subsurface flow constructed wetlands at varying hydraulic loading rates - Zhang, Dong Qing (2013)
Determining the fate of emerging organic contaminants in an aquatic ecosystem is important for developing constructed wetlands (CWs) treatment technology. Experiments were carried out in subsurface flow CWs in Singapore to evaluate the fate and transport of eight pharmaceutical compounds. The CW system included three parallel horizontal subsurface flow CWs and three parallel unplanted beds fed continuously with synthetic wastewater at different hydraulic retention times (HRTs). The findings of the tests at 2–6 d HRTs showed that the pharmaceuticals could be categorized as (i) efficiently removed compounds with removal higher than 85% (ketoprofen and salicylic acid); (ii) moderately removed compounds with removal efficiencies between 50% and 85% (naproxen, ibuprofen and caffeine); and (iii) poorly removed compounds with efficiency rate lower than 50% (carbamazepine, diclofenac, and clofibric acid). Except for carbamazepine and salicylic acid, removal efficiencies of the selected pharmaceuticals showed significant (p < 0.05) enhancement in planted beds as compared to the unplanted beds. Removal of caffeine, ketoprofen and clofibric acid were found to follow first order decay kinetics with decay constants higher in the planted beds than the unplanted beds. Correlations between pharmaceutical removal efficiencies and log Kow were not significant (p > 0.05), implying that their removal is not well related to the compound’s hydrophobicity.